Size Effect in Normal- and High-Strength Concrete with Different Notches under the Axial Load - Koç, V.; Şener, S. (ASCE-Amer Soc Civil Engineers, 2009)
This study investigated the fracturing of concrete under triaxial compression. The experimental program involved size effect tests of compression fractures of cylindrical specimens with small notches, large notches, and holes. The geometrically similar columns of large (λ = 32), medium (λ = 16), and small (λ = 8) slenderness using a size range of 1:2:4:8 (8 for only medium slenderness) were tested. The study's columns were built of normal- and high-strength concrete, in which the maximum aggregate size was 10 mm. A strong size effect was observed in the results. It is shown that, with increasing strength, the size effect becomes more pronounced as the brittleness is increased. © 2009 ASCE.
Keywords: Axial Loads; Concrete Columns; Concrete Structures; Concrete Tests; Failure Loads; High Strength Concrete; Size Effect; Slenderness Ratio